Behavior of cold-formed steel shear walls sheathed with high-capacity sheathing. (15th December 2020) - Derveni, Fani; Gerasimidis, Simos; Peterman, Kara D.
Highlights: Evaluation of fiber cement board and steel-gypsum composite board sheathing. Experimental investigation of cold-formed steel to sheathing shear connections. Hysteretic characterization of cold-formed steel to sheathing connections. Fastener-based finite element modeling of sheathed cold-formed steel shear walls. Design recommendations of high-capacity sheathed cold-formed steel shear walls. Abstract: Cold-formed steel (CFS) framed buildings have shown potential towards innovative and efficient building design in high seismic regions. The objective of this study is to expand the knowledge and breadth of design options of CFS construction into higher capacity lateral force resisting systems; as such, the lateral performance of CFS shear walls sheathed with fiber cement board (FCB) and composite steel-gypsum (SG) panels are the focus of this work. Three-dimensional finite element shell modeling is used by focusing on the impact of sheathing type, screw type and fastener pattern. The computational method includes fastener-based modeling which necessitates the use of experimentally-derived connection behavior. An experimental program of monotonic and cyclic fastener testing was conducted to provide shear response of CFS-to-sheathing connections with various sheathings (FCB, SG), screws, and screw spacing. Monotonic connection means are derived from the experiments and introduced in the finite element model. The numerical results demonstrate significant capacity benefits and different failure modes from traditional wood-sheathed shear walls. This work not only aims to provide an innovative and accurate computational tool for FCB- and SG-sheathed shear walls to the research community, but also to expand CFS practice through higher capacity design options. To enable adoption by practitioners, prescriptive design recommendations are provided. As the developed finite element model is computationally expensive, Pinching4 parameters from the cyclic testing are also provided to aid in the development of reduced-order models.